O incidente de deslocamento de competência para a Justiça Federal e a sua efetividade na defesa dos direitos humanos: o caso Manoel Mattos - Porto, Luana Cavalcanti (2017)
The Competence of Displacement Incident (CDI), inserted in the Brazilian legal system by Constitutional Amendment no. 45/2004, through the 5th paragraph in article 109 of the Brazilian Federal Constitution, provides the federalization of the trial in cases of proven inertia of the local public power to investigate serious violations of human rights under the scope of international treaties to which the Brazilian State is a signatory. In this context, this dissertation aims to evaluate the CDI as an effective mechanism in the defense of serious human rights violations in its pioneering application to the case of the lawyer and human rights defender, Manoel Mattos, who was assassinated for denouncing the actions of extermination groups that counted with the participation of public power agents that sought to promote a "social cleansing" on the border between the municipalities of Pedras de Fogo (PB) and Itambé (PE), known as the border of fear. In order to subsidize this proposal, bibliographical and documentary research has addressed issues related to the participation of public agents in death squads since the time of the military dictatorship, the policies to protect human rights defenders in Brazil, the operation and application of the CDI to the cases submitted to the Superior Court of Justice (SCJ) and, in detail, to the Manoel Mattos case. Likewise, in order to bring the subject closer to the reality investigated, a qualitative research was conducted with eleven respondents directly involved in the case, as well as a quantitative research, through the analysis of the public policy indicators in these two municipalities. The results show that the CDI applied to the case has showed itself as an effective mechanism for defending human rights, since the criteria for federalization were met, enabling criminal prosecution and the promotion of justice through the trial and conviction of two defendants who planned and participated in the execution of Manoel Mattos and the end of the historical impunity of the death squads, especially in Paraíba. In addition to the trial, the case becomes a paradigm, as it brings debates to different levels, rescues the appreciation of human rights defenders and maintains the Brazilian commitment to the international human rights community. Keywords: human rights; Competence displacement incident (CDI); Manoel Mattos; death squads.